Familial glucocorticoid deficiency presenting with generalized hyperpigmentation in adolescence. Report of three siblings - Shivaprasad, K. S. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Familial glucocorticoid deficiency (FGD) is a rare autosomal recessive disorder characterized by glucocorticoid deficiency, high ACTH levels and normal mineralocorticoid levels. FGD is caused due to defects in adrenocorticotropic hormone (ACTH) signaling. The defect can be caused by mutations in genes encoding the ACTH receptor (melanocortin 2 receptor) or its accessory protein. PATIENTS: Here we report three siblings with FGD. The second in order of siblings presented at an age of 15 years with history of diffuse hyperpigmentation since childhood. Their parents were non consanguineous. The patients were hyperpigmented and taller compared with their parents. None of the siblings had ambiguous genitalia or neurological abnormalities. There was no history of tuberculosis in the family. Biochemical investigations revealed low serum cortisol (<1 μg/dl) and elevated plasma ACTH (>1250 pg/ml). Serum electrolytes, aldosterone, and plasma renin activity was normal. Based on the above mentioned data, a provisional diagnosis of FGD was made after ruling out the common causes of glucocorticoid deficiency. CONCLUSION: FGD is a rare autosomal recessive disorder which causes isolated glucocorticoid deficiency. Unawareness about the condition may lead to delayed diagnosis and treatment, which are associated with high rates of morbidity and mortality. Once a diagnosis is made it is easily treatable.